Distinct brain perfusion pattern associated with CSF biomarkers profile in primary progressive aphasia. Issue 7 (4th June 2012) - Kas, Aurélie; Uspenskaya, Olga; Lamari, Foudil; de Souza, Leonardo Cruz; Habert, Marie-Odile; Dubois, Bruno; Teichmann, Marc; Sarazin, Marie
Abstract : Objective: A new classification of primary progressive aphasia (PPA) was recently proposed to differentiate between non-fluent aphasia (NF-PPA), semantic variant of PPA (S-PPA) and logopenic aphasia (LPA) by their phenotypic presentations. CSF biomarkers (BM) may differentiate PPA with atypical Alzheimer's disease (AD) that presents with LPA from PPA with frontotemporal lobe degeneration that presents with either NF-PPA or S-PPA. Single photon emission computed tomography (SPECT) was used to investigate brain hypoperfusion differences among PPA subtypes according to their CSF AD profiles. Methods: 34 PPA patients underwent lumbar puncture and brain perfusion SPECT. PPA patients were classified into two subgroups according to theAβ42 :tau ratio: PPA BM positive (with an AD CSF profile) and PPA BM negative (not having an AD CSF profile). The biological classification was made while blind to the phenotypical presentation. The brain perfusion profiles of the PPA subgroups were compared with those of 24 healthy subjects. Results: PPA BM positive patients had left-side predominant hypoperfusion in the temporoparietal cortex that extended to the dorsolateral prefrontal cortex and perisylvian region while PPA BM negative patients had hypoperfusion that was predominant in the temporal poles (p<10 −4 corrected). Conclusion: Distinct hypoperfusion patterns in PPA BM positive and PPA BM negative patients were observed, similar to those that have been described for S-PPA and LPA. These results support using CSF biomarkers to classify PPA.